"But, We Don't Have a Library": Exploring Approaches to Addressing Branch Campuses' Library Needs. Issue 2 (2nd April 2016) - Hostetler, Kirsten; DeSilva, Michele
Abstract : Librarians at Central Oregon Community College's Barber Library explored how to best serve the needs of three satellite campuses across a large geographic region. While initially intending to start an embedded librarianship program, a pair of surveys showed the relationships and awareness necessary for the foundation of such a program were lacking. Using the information gathered in the surveys, the authors attempted to identify and implement methods for building better relationships and greater library awareness across all campuses.